Role of ineffective erythropoiesis in the anaemia of rheumatoid arthritis. Issue 2 (April 1977) - Samson, D; Halliday, D; Gumpel, J M
Abstract : The importance of inadequate haemoglobin synthesis and ineffective erythropoiesis in the anaemia of rheumatoid arthritis was studied by measuring the incorporation of 15N glycine into haemoglobin haem and early labelled bilirubin in a patient with severe anaemia before and after response to gold therapy. Initially, total erythroid haem turnover was decreased but haem turnover due to ineffective erythropoiesis was markedly increased, accounting for 29% of total erythroid haem turnover. Gold therapy resulted in marked clinical improvement, accompanied by a rise in haemoglobin to normal. Total erythroid haem turnover increased and the percentage ineffective erythropoiesis fell to normal. Ineffective erythropoiesis may thus be an important reversible factor in the production of the anaemia of rheumatoid arthritis.